A Eucharistic Pedagogy: Gospel Parables and Teachings in Simone Weil's "On the Right Use of School Studies". Issue 1 (June 2022) - Lang Hearlson, Christy
Abstract : This article examines biblical allusions in Simone Weil's "On the Right Use of School Studies, " in which she argues that study can train our attention to God and neighbor. Focusing on Weil's use of Jesus' teachings that mention bread, meals, and table service, this article reveals an underlying theme of Eucharist (communion) in Weil's essay on study. Together with Weil's comment that studies are "like a sacrament, " this analysis suggests that Weil offers a "eucharistic pedagogy" shaped by her mystical theology of Eucharist, a theology itself shaped by George Herbert's English-language poem "Love." Throughout, the article compares Weil's original French with its English translation, noting where the translation obscures her use of the Bible or her theology, and it also examines the Greek biblical text, since Weil read the New Testament in its Greek original. The article concludes with a critique of Weil's educational vision, which relies on a dyadic vision of eucharist, and suggests that a communal vision of eucharist can support a social vision of education.